Poetics, plays, and performances : the politics of modern Indian theatre - Dalmia, Vasudha, 1947- (New Delhi ; Oxford : Oxford University Press, 2008)
Addressing the political and aesthetic concerns of modern Indian theatre, propelled by the urban interest in folk theatre and the popularity of Brecht in connection with this, this work focuses on the political aspects, as portrayed in modern Indian theatre.
Originally published: 2006.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Theater -- Political aspects -- India -- History -- 20th century